Low-energy biomass pretreatment with deep eutectic solvents for bio-butanol production. (November 2017) - Procentese, Alessandra; Raganati, Francesca; Olivieri, Giuseppe; Russo, Maria Elena; Rehmann, Lars; Marzocchella, Antonio
Highlights: Reaction time and temperature for Deep Eutectic Solvent pretreatment were investigated. Glucose yields of 94.9% were obtained after pretreatment at 150 °C for 16 h. Biobutanol was produced after lettuce leaves pretreated with DES. Energy required for DES pretreatment was assessed 72% lower than steam explosion. The Net Energy Ratio (NER) for butanol production via DES pretreatment was assessed. Abstract: Waste lettuce leaves – from the "fresh cut vegetable" industry – were pretreated with the deep eutectic solvent (DES) made of choline chloride – glycerol. Reaction time (3–16 h) and the operation temperature (80–150 °C) were investigated. Enzymatic glucose and xylose yields of 94.9% and 75.0%, respectively were obtained when the biomass was pretreated at 150 °C for 16 h. Sugars contained in the biomass hydrolysate were fermented in batch cultures of Clostridium acetobutylicum DSMZ 792. The energy consumption and the energy efficiency related to the DES pretreatment were calculated and compared to the most common lignocellulosic pretreatment processes reported in the literature. The DES pretreatment process was characterized by lower energy required (about 28% decrease and 72% decrease) than the NAOH pretreatment and steam explosion process respectively. The Net Energy Ratio (NER) value related to butanol production via DES biomass pretreatment was assessed.